The Influence of Intellectual Capital Disclosure and Profitability on Value Company - Putra, Gerry Hamdani; Marlina, Marlina (El-Barka Journal of Islamic Economics and Business, 2021)
The Company's value reflects the assets owned by the company. This study aims to examine the effect of intellectual capital disclosure and profitability on firm value. The Population are manufacturing companies listed on the Indonesia Stock Exchange in 2016 ”“ 2020. The samples of this study are forty-four companies listed in Indonesia Stock Exchange (IDX) selected by using purposive sampling method. The data analysis method used is multiple regression model. Based on the hypothesis tasted proves that the intellectual capital disclosure and profitability have the positive and significant effect on firm value. Firm value is able to provide maximum welfare to shareholders. An increase in share prices can reflect the company's assets.